모래놀이치료를 적용한 모-유아 중심의 애착관계 개선 프로그램 개발 및 효과 연구 - 김미정(Mi Jung Kim); 정계숙(Kai Sook Chung) (Korean Journal of child studies, 2006)
This study aimed to improve mother-child attachment relationship by goal-corrected partnership. The subjects of this study were three 5- to 6-year-old children with insecure attachment patterns and their mothers. The Mother-Child Attachment Intervention Program with Applied Sand-Play Therapy consisted of two steps, sand-play therapy for each mother and child for 8 sessions and three different intervention activities(activities for children only, mother education activities and mother-child cooperative activities) conducted for 12 sessions. Each of the therapy and the activity sessions ran for 40 and 80 minutes weekly. After completing the program, the mothers' representation of their parents changed positively, but the changes depended on their attachment classifications. All of the mothers' warm/responsive parenting behaviors increased despite some individual differences.